Patchouli Seeds Production and Handling to Provide Good Quality of Seed - SUKARMAN, .; WAHYUNI, SRI (Puslitbang Perkebunan, 2013)
Patchouli (Pogostemon cablin Benth.) is a primary essential oil plant of Indonesia. It produces patchouli oil, and provides almost 90 % of world essential oil. To maintain the stability of market demand, it is necessary to develop sustainable production system of patchouli plantation. For the purpose, providing high quality seeds supply is required. In order to meet the seed standard, some requirement should be considered e.q. superior variety used, the suitability of land and climate for production area, cultivation technique, diseases and pest management control. Plant materials are developed by cuttings. The storage of cuttings are very limited, but they are voluminous and voluminous characters. Distributing the seeds need high cost due to packaging system and has limited time to keep the high seed viability. Packaging technique to keep cuttings remain fresh should be developed. To overcome the avaibility of seed supply at patchouli area development, in the seed production should be developed in the same area. Further more, high seed quality should be guaranted by certification process. This paper aims to inform technology production and handling system in order to get the high quality of patchouli. Key word: Pogostemon cablin, patchouli, seed production, seed handling.